2014
DOI: 10.4238/2014.march.31.4
|View full text |Cite
|
Sign up to set email alerts
|

Association between BMP-2 and COL6A1 gene polymorphisms with susceptibility to ossification of the posterior longitudinal ligament of the cervical spine in Korean patients and family members

Abstract: ABSTRACT. COL6A1 and BMP-2 genes have been implicated in ossification of the posterior longitudinal ligament (OPLL) susceptibility in Japanese and Chinese Han populations. However, no study has yet investigated the DNA of unaffected family members of patients with OPLL. This study investigated differences in genetic polymorphisms of BMP-2 and COL6A1 between Korean patients with OPLL and their family members (with and without OPLL). A total of 321 subjects (110 patients with OPLL and 211 family members) were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Chronic compression of the spinal cord and nerve root leads to spinal cord compression symptoms and radiculopathy in patients with OPLL. The severity of the symptoms is associated with the size and segmentation of the ossifying ligament, and 70% of OPLL occurs in the cervical spine, whereas 15% occurs in the thoracic spine (1). Notably, as early as 1972, researchers reported that thoracic OPLL (T-OPLL) can cause thoracic spinal stenosis (2).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic compression of the spinal cord and nerve root leads to spinal cord compression symptoms and radiculopathy in patients with OPLL. The severity of the symptoms is associated with the size and segmentation of the ossifying ligament, and 70% of OPLL occurs in the cervical spine, whereas 15% occurs in the thoracic spine (1). Notably, as early as 1972, researchers reported that thoracic OPLL (T-OPLL) can cause thoracic spinal stenosis (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, Liu et al (2010) reported no significant effect of the rs2276255 SNP on the risk of OPLL or OLF development [20], in contrast to Tanaka et al's finding of a weak significant effect (p = 0.048). Further contradiction in the COL6A1 gene is seen in Kong et al's (2007) finding that the promoter (−572) SNP T allele was associated with a 2.94 times greater risk of OPLL (p = 0.0003), while found no significant effect (p = 0.282) [22]. Liu et al (2010) found no effect of one additional SNP (rs9978314) on the risk of OPLL or OLF development [20].…”
Section: Spinal Pathologymentioning
confidence: 99%
“…Yan et al (2013) also found the Ser37Ala SNP to be associated with increased risk (p < 0.001) [21], although a more recent study that compared OPLL patients to their family members found no effect of either the Ser87Ser or Ser37Ala SNPs on risk of OPLL (p = 0.411, p = 0.670, respectively) [22]. Additionally, the 570A>T SNP in the BMP2 gene was not found to be significantly associated with risk of OPLL [21].…”
Section: Spinal Pathologymentioning
confidence: 99%
“…Other studies have shown similar findings and linked this SNP to ossification of the ligamentum flavum and diffuse idiopathic skeletal hyperostosis (50, 51). However, a study of these COL6A1 SNPs in a Korean population revealed conflicting results (52). Although significant data support the two collagen molecules as contributing to the pathogenesis of OPLL, lack of data congruency has made reliable conclusions difficult to make, likely due to disease heterogeneity.…”
Section: Ossification Of the Posterior Longitudinal Ligamentmentioning
confidence: 99%
“…It is thought that distinct genetic characteristics define these seemingly similar, but quite clinically different syndromes. Our systematic review identified six works in the literature (Table 2) (52, 8387) that identified genetic contributions for DS. The quality of the data is relatively limited (Level III studies) but provides some insight into potential genetic mechanisms for disease pathogenesis that could potentially be used in future studies.…”
Section: Degenerative Lumbar Scoliosismentioning
confidence: 99%